Molecular and cellular mechanisms of itch sensation and the anti-itch drug targets - Sun Meng; Chen Zhen-ru; Ding Hui-juan; Feng Jing (Acta Pharmacologica Sinica, 2025)
Itch is an uncomfortable feeling that evokes a desire to scratch. This protective reflex can effectively eliminate parasites that invade the skin. When itchy skin becomes severe or lasts for more than six weeks, it has deleterious effects on both quality of life and productivity. Despite decades of research, the complete molecular and cellular coding of chronic itch remains elusive. This persistent condition often defies treatment, including with antihistamines, and poses a significant societal challenge. Obtaining pathophysiological insights into the generation of chronic itch is essential for understanding its mechanisms and the development of innovative anti-itch medications. In this review we provide a systematic overview of the recent advancement in itch research, alongside the progress made in drug discovery within this field. We have examined the diversity and complexity of the classification and mechanisms underlying the complex sensation of itch. We have also delved into recent advancements in the field of itch mechanism research and how these findings hold potential for the development of new itch treatment medications. But the treatment of clinical itch symptoms still faces significant challenges. Future research needs to continue to delve deeper, not only to discover more itch-related pathways but also to explore how to improve treatment efficacy through multitarget or combination therapy.